2018
DOI: 10.5433/1679-0359.2018v39n3p1225
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural answers and chemical composition of Massai grass under different nitrogen doses and urea sources

Abstract: Under the hypothesis that modifying nitrogen sources and doses could increase nitrogen fertilization efficiency and productivity and improve forage quality, this study aimed to evaluate the morphological composition, structural characteristics and chemical composition of Panicum maximum cv. Massai forage cultivated under different urea sources (common and coated with Policote ResumoSob a hipótese de aumento da eficiência da adubação nitrogenada quanto ao uso de diferentes fontes e doses de nitrogênio, aliado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…During dry season Tobiatá,Mombasa,Tanzania,Vencedor,and Massai had 7.09,6.24,6.13,6.72, and 7.82% of protein content. These values were higher than those found in commercial cultivars in important tropical livestock areas (Costa et al, 2017Silva T.V.S et al, 2017Silva et al, 2018. However, in the same research location where the experiment took place, and with a similar number of recovery days and average height in Massai, obtained results were higher than 14.20% (Ruiz et al, 2015).…”
Section: Discussionmentioning
confidence: 82%
“…During dry season Tobiatá,Mombasa,Tanzania,Vencedor,and Massai had 7.09,6.24,6.13,6.72, and 7.82% of protein content. These values were higher than those found in commercial cultivars in important tropical livestock areas (Costa et al, 2017Silva T.V.S et al, 2017Silva et al, 2018. However, in the same research location where the experiment took place, and with a similar number of recovery days and average height in Massai, obtained results were higher than 14.20% (Ruiz et al, 2015).…”
Section: Discussionmentioning
confidence: 82%
“…During the dry season, Tobiatá, Mombasa, Tanzania, Vencedor, Massai, and Coloniao had protein content of 7.09, 6.24, 6.13, 6.72, 7.82, and 8.30%, respectively. These values were higher than those found in commercial cultivars in important tropical livestock areas (dos da Silva et al, 2018). However, in the same research location where this experiment took place, and with a similar number of regrowing days and average height in Massai, Ruiz et al (2015) showed 14.20% CP.…”
Section: Seasonmentioning
confidence: 54%
“…09, 6.24, 6.13, 6.72, 7.82, and 8.30%, respectively. These values were higher than those found in commercial cultivars in important tropical livestock areas (dos Costa et al, 2017;Silva et al, 2017;da Silva et al, 2018). However, in the same research location where this experiment took place, and with a similar number of regrowing days and average height in Massai, Ruiz et al (2015) showed 14.20% CP.…”
Section: Seasonmentioning
confidence: 59%